Interdisciplinarity as a necessity in theory and practice of surdologopaedics - Liwo, Helena (Interdyscyplinarne aspekty diagnozy i terapii logopedycznej, 2020)
The complex nature of the language communication is largely manifested in language disabilities, this resulting in the necessity of multi-aspect research on the condition of individuals with language disabilities which, in turn, belongs to the field of logopaedics. It applies especially to surdologopaedics. The object of this subdiscipline is initiating or improvement of language development in people with hearing deficiencies. Use of the interdisciplinary procedure of cochlear implantation enables the individuals who suffer from major hearing impairments to develop their hearing and language skills. For this treatment to be effective, the current stereotype, in which individuals with hearing disability are considered deaf-mute, must be abandoned. It is also applies both to the theoretical perspective, which combines the philosophical, biological, psychological and social aspects of the issue of deafness, and to the practical perspective, which covers diagnosing and implanting hearing organs, as well as pedagogic and surdologopaedic methods.